2017
DOI: 10.1002/eji.201746951
|View full text |Cite
|
Sign up to set email alerts
|

Typical antimicrobials induce mast cell degranulation and anaphylactoid reactions via MRGPRX2 and its murine homologue MRGPRB2

Abstract: Mast cells are unique immune cells that function as sentinels in host defence reactions, including immediate hypersensitivity responses and allergic responses. The mast cell-specific receptor named MAS-related G protein-coupled receptor X2 (MRGPRX2) triggers mast-cell degranulation, a key process in anaphylactoid reactions. It is widely observed that antimicrobials can induce pseudo-allergic reactions (i.e. IgE-independent mechanism) with symptoms ranging from skin inflammation to life-threatening systemic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 28 publications
3
28
0
3
Order By: Relevance
“…Some reports have also provided evidence that PF can treat anaphylactic rhinitis and allergic asthma (Gaudenzio et al, ). Activation of MRGPRX2 can induce the release of several proinflammatory mediators including, interleukins, tumor necrosis factor, and prostaglandin D2 which can induce itch (Zhang et al, ). MRGPRX2 showed a correlation to two specific itchy conditions, namely, red man syndrome associated with vancomycin and atopic dermatitis (Azimi, Reddy, & Lerner, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have also provided evidence that PF can treat anaphylactic rhinitis and allergic asthma (Gaudenzio et al, ). Activation of MRGPRX2 can induce the release of several proinflammatory mediators including, interleukins, tumor necrosis factor, and prostaglandin D2 which can induce itch (Zhang et al, ). MRGPRX2 showed a correlation to two specific itchy conditions, namely, red man syndrome associated with vancomycin and atopic dermatitis (Azimi, Reddy, & Lerner, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the receptor on MCs that specifically binds non‐immune ADR‐causing drugs was reported to be MRGPRX2, a G protein‐coupled receptor found almost exclusively on MCs . The mouse analogue of this receptor is Mrgprb2, which is found mostly on connective tissue MCs . Although several drugs have been reported to cause adverse reactions in humans, only few have been shown to evoke a similar reaction in mice .…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, XZ Dong et al . first found that Mas‐related G protein‐coupled receptor X2 (MRGPRX2) specific expressed on mast cells was related to pseudo‐allergic reactions and could be used as a potential target for therapy . Basing on the previous research, PF has been proved to be effective in alleviating allergic or pseudo‐allergic reaction, however, whether it exerted the anti‐pseudo‐allergic pharmacological effects by targeting to MRGPRX2 receptor remains unknown.…”
Section: Introductionmentioning
confidence: 99%